PROMOTING DEEP LEARNING THROUGH PERSONAL REFLECTIVE E-JOURNALING: A CASE STUDY - van Breda, Adrian Daisy; Agherdien, Najma (Social Work/Maatskaplike Werk, 2012)
Social work educators are in the business of forming social workers. We are concerned not only with the transmission of knowledge and skills; we want to shape the whole person to become a professional social work practitioner (Dempsey, Halton & Murphy, 2001). To achieve this, we strive to facilitate deep learning among students – the kind of learning that enables students to locate themselves in their learning (Collins & Van Breda, 2010), to construct personal meaning (Clare, 2007). A deep learning approach, Marton and Säljö (1976) argue, involves sense making and having multiple understandings of our world, while a surface learning approach involves rote learning or memorisation of facts. Entwistle and Ramsden (1983) add a third approach known as a strategic learning approach, which entails students purposefully managing their time, study methods and developing an awareness of assessment processes.